Modelling maritime interaction in the Aegean Bronze Age, II. The Theran eruption and Minoan palatial collapse - Rivers,RJ; Evans,TS; Knappett,C (Antiquity: a quarterly review of archaeology, 2011)
What was the effect on Late Minoan civilisation of the catastrophic destruction of Akrotiri on Thera (Santorini) by volcanic eruption? Not much, according to the evidence for continuing prosperity on Crete. But the authors mobilise their ingenious mathematical model (published in Antiquity 82: 1009–1024), this time to show that the effects of removing a major port of call could have impacted after an interval, as increased costs of transport gradually led to ever fewer routes and eventual economic collapse.